(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Ectopic Cushing syndrome is an exceptionally rare condition in the pediatric population, particularly when arising from a thymic carcinoid tumor. We report the case of a six-year-old boy who presented with generalized swelling, moon face, acne, weight gain, hyperpigmentation, hypertension, and seizures. Biochemical evaluation demonstrated elevated cortisol and ACTH levels, unsuppressed by dexamethasone, indicating ACTH-dependent Cushing syndrome. Imaging revealed an anterior mediastinal mass, which was surgically excised and confirmed histologically as a thymic carcinoid tumor. Postoperatively, the patient required corticosteroid replacement, with gradual improvement of clinical features on follow-up. This case underscores the importance of considering ectopic ACTH secretion in children with rapidly progressive hypercortisolism and highlights the need for timely diagnosis and multidisciplinary management for favorable outcomes. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 60-65]